Researching the Gap between Foodstuff's Attractiveness and Real Nutritional Profile – Prerequisite for Strengthening Nutrition Education and Consumer Rights Protection - Bogdan Cristian Onete; Lelia Voinea; Alina Filip; Razvan Dina (Amfiteatru Economic Journal, 2014)
Consumer's health protection has become a major concern of global public policies, given that overweight and obesity have alarmingly increased, particularly among children and teens. The paper addresses one of the current problems caused by globalization, namely the obvious tendency of young people to choose food products based on organoleptic features and to disregard nutritional quality, with negative consequences on health. An exploratory marketing research was conducted among students for identifying the perceived importance of the sensorial dimension of food products and understanding key dimensions of buying decision process among youth. SAIN–LIM method was used to determine the nutritional profile of foodstuffs with special organoleptic features. Research results clearly show that in industrial foodstuff there is a gap between product attractiveness, which is based on exceptional sensorial properties, perceived by young consumers and real nutritional value of foods, which frequently translates into unbalanced nutritional profiles. To have a balanced diet and a healthy lifestyle, young consumers need to be informed that a tasty and good looking foodstuff is not necessarily healthy. Youth need to be properly educated in order to understand the close relationship between diet, weight and health and to develop a responsible food consumption behavior.
Keywords: M10; M31; Z10; 330; sensorial properties; nutritional value; food buying behavior; marketing research; communication campaign; nutrition education; consumer rights